Analisis Kesiapan Guru Sekolah Dasar dalam Implementasi Pembelajaran Coding: Systematic Literature Review - Lusiana Sae, Herlin; Nuni Widiarti; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The integration of coding instruction in elementary schools has become increasingly urgent in response to 21st-century skills demands, particularly computational thinking, and is encouraged by policies such as the Merdeka Curriculum in Indonesia. However, successful implementation heavily depends on teacher readiness, which remains a significant challenge. This study aims to identify and analyze the dimensions of teacher readiness and the factors influencing it in the implementation of coding instruction in elementary schools. A Systematic Literature Review (SLR) with the PRISMA protocol was employed. Literature searches were conducted in Scopus, Web of Science, ERIC, and Google Scholar for articles published between 2015 and 2025. A total of 33 peer-reviewed articles meeting the inclusion criteria were further analyzed. The synthesis results indicate that teacher readiness is a multidimensional construct encompassing four main dimensions: (1) technical competence readiness (mastery of coding and computational thinking), (2) pedagogical readiness (project-based learning strategies and scaffolding), (3) psychological readiness (self-efficacy and attitudes toward technology), and (4) institutional readiness (school support, infrastructure, and professional training). Factors such as continuous professional development, policy support, prior experience, and technology access were identified as key determinants influencing readiness. Theoretically, this study reinforces the multidimensional framework of digital teacher readiness and extends models like TPACK by integrating psychological and institutional factors. Practically, these findings underscore the need for sustained, practice-based teacher training programs, integrated policy support, and adequate infrastructure to create an ecosystem conducive to implementing coding instruction in elementary school